2019
DOI: 10.1038/s41598-019-48023-5
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Radiomics Approach to Quantifying Pulmonary Function in CT Images

Abstract: Contemporary medical imaging is becoming increasingly more quantitative. The emerging field of radiomics is a leading example. By translating unstructured data (i.e., images) into structured data (i.e., imaging features), radiomics can potentially characterize clinically useful imaging phenotypes. In this paper, an exploratory radiomics approach is used to investigate the potential association between quantitative imaging features and pulmonary function in CT images. Thirty-nine radiomic features were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…The present study revealed that two coarse texture features, LowGreyLevelRunEmphasis_AllDirection_offset2_SD (ρ = −0.63) and ShortRunLowGreyLevelEmphasis_AllDirection_offset9_SD (ρ = −0.70), were found to be negatively correlated with DLCO. Similar results were reported by Barjaktarevic et al [29]. Low Gray Level Run Emphasis (LGLRE) is only a measure of CT attenuation, while Short Run Low Gray Level Emphasis (SRLGLE) is a joint-measure of CT attenuation and HU heterogeneity.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The present study revealed that two coarse texture features, LowGreyLevelRunEmphasis_AllDirection_offset2_SD (ρ = −0.63) and ShortRunLowGreyLevelEmphasis_AllDirection_offset9_SD (ρ = −0.70), were found to be negatively correlated with DLCO. Similar results were reported by Barjaktarevic et al [29]. Low Gray Level Run Emphasis (LGLRE) is only a measure of CT attenuation, while Short Run Low Gray Level Emphasis (SRLGLE) is a joint-measure of CT attenuation and HU heterogeneity.…”
Section: Discussionsupporting
confidence: 87%
“…A high HGLRE value indicates a dense and homogenous tissue, while a low value indicates a low attenuating and heterogeneous tissue. The relationship between HGLRE and FEV1 observed in the present study means that: (1) patients with normal spirometry may have a dense and homogenous lung; and (2) patients with abnormal spirometry may also have a low attenuating and heterogeneous lung [29,32].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although the implementation of these approaches and integration of new knowledge arising from these findings into clinical practice will be complex and require extensive validation, future ML pipelines will be an integral component of the pathologist’s workflow as decision support tools. Indeed, some of these algorithms are already making their way into routine practice in the field of radiation oncology 42 , 124 , 125 . The ultimate challenge will be the integration and implementation of computational image analysis-generated data with other knowledge domains to establish fused datasets and associated morpho-omic classifications, prognostications and predictions for kidney diseases at the individual patient level (that is, fused morpho-omic signatures ).…”
Section: Applications and Challengesmentioning
confidence: 99%